Impact of Sanctions on Global Energy Markets and International Relations: A Case Study of Russia (Journal of Political Science and International Relationship, 2025)
This research looks into how international sanctions affect global energy markets and international relations, focusing on Russia. After the West, mainly the U.S. and EU, imposed sanctions due to Russia’s military actions in Ukraine, the usual energy trade has been thrown off balance. Russia, being one of the biggest energy exporters, has felt the impact deeply. The sanctions have affected oil and gas production, funding, technology sharing, and foreign investments, leading to less efficient energy use and halted technological progress. As a result, Russia has had to change its trade routes towards countries like China and India instead of sticking with traditional Western partners. These sanctions also caused energy prices to fluctuate, affecting both rich and developing nations. Countries that rely on energy imports are now looking for new suppliers and investing in different energy sources, while Russia is trying to renegotiate trade deals under new political and financial conditions. This situation shows how global energy security and political relations are tied together and shows the unexpected fallout from economic sanctions. This study finds that while sanctions are meant to pressure political leaders, they can have wider effects that change the global economy. Russia’s sanction case shows that energy sanctions can push some political agendas which can also lead to new international relationships among nations and faster changes in global energy practices. The results suggest that policymakers need to think carefully about the long-term impacts of sanctions on international stability and the global energy landscape.